2018
DOI: 10.1017/ice.2018.247
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of resistant Gram-negative bacteria to healthcare personnel gowns and gloves during care of residents in community-based nursing facilities

Abstract: Objective: To estimate the risk of transmission of antibiotic resistant Gram-negative bacteria (RGNB) to gowns and gloves worn by healthcare personnel (HCP) when providing care to residents of community-based nursing facilities in order to identify the types of care and resident characteristics associated with transmission. Design: Prospective observational study Settings and participants: Residents and HCP from 13 community-based nursing facilities in Maryland and Michigan Methods: Perianal swabs were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…The rate of ARO acquisition was similar to rates reported in prior studies of transmission of R-GNB to the gloves of NF HCP and was lower than rates observed in MRSA transmission. [22][23][24] Pathogen acquisition was diverse, with relatively equal numbers of VRE, MRSA, and R-GNB isolated. In most cases, the relevant pathogen was also cultivated from the patient or environment, with identical PFGE patterns in a small subset of tested isolates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of ARO acquisition was similar to rates reported in prior studies of transmission of R-GNB to the gloves of NF HCP and was lower than rates observed in MRSA transmission. [22][23][24] Pathogen acquisition was diverse, with relatively equal numbers of VRE, MRSA, and R-GNB isolated. In most cases, the relevant pathogen was also cultivated from the patient or environment, with identical PFGE patterns in a small subset of tested isolates.…”
Section: Discussionmentioning
confidence: 99%
“…High rates of ARO acquisition were observed with both high-risk (eg, incontinence care, dressing assist) and low-risk (eg, repositioning, patient transfers) activities. Prior work by Blanco et al 23 found assisting residents with dressing, bathing, hygiene, incontinence care, and transfers, in addition to showering, to be the highest risk activities for HCP in the NF setting, each with a R-GNB transmission rate of >12%. Potential exposure to mucous membranes or body fluid among these activities is variable; sustained patient contact may be a more important risk factor for ARO acquisition among HCP in the NF setting; however, further studies are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Activities defined as high risk for transmission of pathogens included cleaning toilets and showers, handling soiled linens, and assisting residents with bathing and toileting. 2…”
mentioning
confidence: 99%
“…Accordingly, nursing home staff also has contact with residents outside of their rooms in dining, bathing, and rehabilitation areas. Several recent studies have examined the transmission of MDROs to healthcare workers while caring for nursing home residents in their rooms, finding that the activities most likely to result in MDRO transmission from residents to healthcare workers are those that involve close contact: assistance with activities of daily living, physical examination, dressing changes, and the care or use of indwelling medical devices …”
mentioning
confidence: 99%
“…Several recent studies have examined the transmission of MDROs to healthcare workers while caring for nursing home residents in their rooms, finding that the activities most likely to result in MDRO transmission from residents to healthcare workers are those that involve close contact: assistance with activities of daily living, physical examination, dressing changes, and the care or use of indwelling medical devices. 4,5 In this issue of the Journal of the American Geriatrics Society, Gontjes et al examine the burden of MDROs recovered in nursing homes from environments outside of resident rooms. 6 In doing so, they are also moving into new territory for infection prevention and control-that of common and rehabilitations areas in nursing homes.…”
mentioning
confidence: 99%